Factors influencing disaster preparedness behaviors of older adults. - Kai-Min Liao; Yih-Jin Hu (PLoS ONE)
This study examines the heterogeneity in disaster preparedness behaviors among older adults and the factors that influence them, with the aim of offering policy recommendations to mitigate casualties among older adults during natural disasters. This is a secondary data analysis of cross-sectional data involving 394 participants aged 65 and above, with data sourced from the seventh wave of the Basic Social Change Survey conducted by Academia Sinica. These cross-sectional data were collected through face-to-face interviews, where interviewers conducted one-on-one questioning to gather general information and assess disaster preparedness. Hierarchical regression analysis was employed to explore the relationship between various factors and disaster preparedness behaviors. Descriptive statistics show that among the six disaster preparedness behaviors, 32.5% of the elderly moved vehicles or household items to a safe location, and 27.2% secured cabinets or large appliances. The remaining four disaster preparedness behaviors-including purchasing disaster insurance, preparing a disaster emergency kit, identifying and planning evacuation locations and routes, and participating in disaster response drills-were exhibited by less than 11.9% of the participants. Hierarchical regression showed that younger age, higher education, lower income, better health, community involvement, disaster experience, and higher perceived risk were associated with increased preparedness among older adults. The study found that most older adults do not invest time or money in disaster preparedness. Government agencies should encourage older adults to participate and account for their heterogeneity, such as through targeted interventions in health promotion, disaster response education, and social support. Initiatives like health check-ups, exercise classes to improve physical fitness, and simple, understandable disaster response courses can enhance risk perception. For high-income groups, emphasizing the importance of disaster preparedness through data and real-life examples is crucial. Older adults should also be encouraged to join community organizations and disaster drills, and a platform for sharing disaster experiences should be established to improve overall disaster resilience.